Slit-lamp measurement of the anterior chamber depth. Issue 3 (March 1986) - Douthwaite, W A; Spence, D
Abstract : A technique is proposed which allows assessment of the anterior chamber depth with a standard table slit-lamp without any extra attachments. A final approximation is made which suggests that a 1 degree change in the angle between the observation and illumination systems of the slit lamp when the end point is reached indicates a change in anterior chamber depth of 0.1 mm.